PENGETAHUAN GIZI, ASUPAN ZAT GIZI, SERTA PEMBERIAN MAKANAN TAMBAHAN DENGAN STATUS GIZI IBU HAMIL: Relationship Of Nutrition Knowledge, Nutrition Intake, Provision Of Supplementary Food With Nutritional Status Of Pregnant Women - Ramdhani, Annisya Nur Rachmi; Agestika, Lina; Srimiati, Mia (Media Gizi Pangan, 2024)
Chronic Energy Deficiency (CED) is still a high nutritional problem in Indonesia with a prevalence of 17.3%. The Gang Kelor Community Health Center, Bogor City, in 2022 recorded that around 7.3% of pregnant women experienced CED. This study aims to determine the relationship between nutritional knowledge, nutritional intake, and provision of supplementary feeding with the nutritional status of pregnant women in the Gang Kelor Community Health Center, Bogor City between February and May 2023. This is a comparative study with a cross-sectional design purposively involving 78 pregnant women. Pregnant women with normal nutritional status had significantly higher nutritional knowledge (p = 0.018), energy intake (p = 0.016), carbohydrate intake (p = 0.047), and fat intake (p = 0.016) compared to pregnant women with CED. Meanwhile, there was no significant relationship between protein intake (p = 0.202). Further, less than 15% pregnant women with CED received supplementary feeding (p = < 0.001). Increasing the intake of essential macronutrients and maternal nutritional knowledge is very important in preventing CED